Fast and Flexible Generation of Conductive Circuits - Amend, Philipp; Hentschel, Oliver; Scheitler, Christian Josef; Baum, Marcus; Heberle, Johannes; Roth, Stephan; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2013)
The functional and geometrical requirements to electronic, optoelectronic and mechatronic devices have significantly increased during the last years. Within the scope of the development and the fabrication of such components a very important aspect is the fast and flexible generation of conductive circuits respectively structures on work-pieces of various dimensions and materials. The presented work gives an overview about three promising laser-based approaches to generate microscopic and macroscopic circuits as well as conductive layers with a thickness in the order of a few hundred nanometers. In addition to processes for the fabrication of conductive structures laser-based soldering of piezo-composites is investigated.
Keywords: conductive circuits; ITO nanoparticles; stereolithography; ADDIMID technology; Molded Interconnect Device; Laser-Beam-Melting; laser-based soldering; piezo-composites